(untitled) (Global Journals of Research in Engineering, 2023)
An RTD or resistance temperature detector is a sensor used to measure temperature Made from either platinum copper or nickel RTDs have a repeatable resistance vs temperature relationship and an operating temperature range of 2000C to 8500C RTDs contain a resistor whose resistance value changes as the temperature changes They have been used for many years to measure temperature in laboratory and industrial processes and have developed a reputation for accuracy repeatability and stability Platinum is a noble metal and has the most stable resistance-temperature relationship over the largest temperature range it is therefore more common than copper or nickel RTDs These devices are used extensively in the nuclear industry for monitoring the water temperature level in the core of nuclear reactor plants such as the family of Light Water Reactors LWRs The RTD element does not respond instantaneously to changes in water temperature within the core of the reactor but rather there is a time delay before the element senses the temperature change and in nuclear reactors this delay must be factored into the computation of setpoints from the probabilistic risk assessment PRA specifically if we are using such a device in the new Advanced Concept Reactor ARC technology of Small Modular Reactors SMRs of Generation IV also known as GEN-IV In this short review first of all we will introduce this known technology in a simple way and then look into its application as in-core instrumentation and control I C within these new-generation reactors